Score Fusion Using Hybrid Bacterial Foraging Optimization And Particle Swarm Optimization (Bfo-Pso) For Hand-Based Multimodal Biometrics - Shanmugasundaram, Karthikeyan (2020)
In recent times of biometric authentication, the influence of swarm intelligence algorithms role-played in enhancing the performance accuracy to a greater extent. Most researches related to Swarm Intelligence (SI) algorithms have done on the particular, due to the need to integrate more than one SI algorithm for better results. Therefore, this research is focused on the hand-based multimodal biometric score fusion which incorporates the scores of hand-based multimodalities and the optimal weights using Hybrid Bacterial Foraging - Particle Swarm Optimization (HBF-PSO) algorithm.